L’insaisissable religion des Taïnos. Esquisse d’anthropologie historique - Giuseppe A. Samonà (Journal de la Société des Américanistes)
The elusive religion of the Taïnos: a historical anthropological outline. Having disappeared shortly after the discovery of the New World, the Tainos today are back in vogue, especially where the zemis are concerned, mysterious multiform objects that had already struck the attention of the earliest Western observers. In this article, these observers, who have too often been overlooked by contemporary anthropology, are revisited in an attempt to draw an outline of what might have been the « religious » thought of the Tainos, the primary characteristic of which is believed to be the cult of the zemis. More speciﬁcally, the author analyzes the eyewitness accounts of Columbus and Pané and underscores their genuinely ethnological quality, particularly in the case of the latter. From this perspective – i.e., that of historical anthropology – certain contemporary anthropological interpretations regarding the « religion » of the zemis appear extremely remote from the Taino culture and surprisingly close to the interpretations fashioned by later chroniclers (especially Pierre Martyr and Las Casas).